2012
DOI: 10.1371/journal.pone.0046300
|View full text |Cite
|
Sign up to set email alerts
|

A Potent Class of GPR40 Full Agonists Engages the EnteroInsular Axis to Promote Glucose Control in Rodents

Abstract: Type 2 diabetes is characterized by impaired glucose homeostasis due to defects in insulin secretion, insulin resistance and the incretin response. GPR40 (FFAR1 or FFA1) is a G-protein-coupled receptor (GPCR), primarily expressed in insulin-producing pancreatic β-cells and incretin-producing enteroendocrine cells of the small intestine. Several GPR40 agonists, including AMG 837 and TAK-875, have been disclosed, but no GPR40 synthetic agonists have been reported that engage both the insulinogenic and incretinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 44 publications
3
135
1
5
Order By: Relevance
“…2015). Since mutagenesis studies suggests that AM1638 does not bind to the arginines Luo et al 2012), the carboxyl group of AM1638 might be coordinated by other charged or hydrophilic residues within the extracellular binding cavity. We have previously shown that K62 2.60 is the third positively charged residues in the extracellular side and potentially could interact with AM1638 (Tikhonova and Poerio.…”
Section: Docking To the Ffa1 Crystal Structurementioning
confidence: 99%
“…2015). Since mutagenesis studies suggests that AM1638 does not bind to the arginines Luo et al 2012), the carboxyl group of AM1638 might be coordinated by other charged or hydrophilic residues within the extracellular binding cavity. We have previously shown that K62 2.60 is the third positively charged residues in the extracellular side and potentially could interact with AM1638 (Tikhonova and Poerio.…”
Section: Docking To the Ffa1 Crystal Structurementioning
confidence: 99%
“…Interestingly, it has been noted that several FFA1 agonists, including 2, 3 and 4, are in fact partial agonists compared with the endogenous fatty acids [62,63,39,73]. Given that 2 (and possibly 3 and 4) is allosteric, this may suggest that allosteric agonists of FFA1 produce different functional outcomes than their orthosteric counterparts.…”
Section: Allosteric Ligands For Ffa1mentioning
confidence: 99%
“…De fait, la majorité des études récentes sont en accord avec le concept que l'hyperinsulinémie induite par les acides gras représente un mécanisme compensatoire face à l'insulinorésistance (voir revue dans [10]), et que cette réponse est compromise par l'inactivation fonctionnelle de GPR40 [15]. Cette notion est corroborée par les effets bénéfiques du traitement par des agonistes de GPR40 sur l'homéostasie glycémique chez les rongeurs [16][17][18][19] et, surtout, chez les patients diabétiques [20,21]. Le récepteur GPR40 peut aussi potentialiser la sécré-tion d'insuline en réponse au glucose par des méca-nismes indirects qui dépendent de la sécrétion des incrétines.…”
Section: Distribution Tissulaire Et Rôle Physiologique Des Récepteursunclassified
“…GPR40 est exprimé dans plusieurs types de cellules entéroendocrines et semble impliqué dans la sécrétion des incrétines en réponse aux acides gras [19,22,23]. L'expression de GPR40 dans les cellules α du pancréas est controversée [24,25], et son rôle dans la sécrétion du glucagon reste à établir de manière concluante [26,27].…”
Section: Synthèse Revuesunclassified
See 1 more Smart Citation